AUDIT TENURE, AUDITOR EXPERIENCE, INDEPENDENCY, AND TASK COMPLEXITY ON AUDIT JUDGEMENT - Arie Pratania Putri; Nur Nabila; Viony Augustin; Fellia Fellia (JRAK, 2021)
Research was conducted in KAP in the area of Medan with the primary data collection method using questionnaire. The sampling was conducted by purposive sampling technique and the sample used in this research was 82 respondent. The method of analysis was used is multiple linear regression analysis using SPSS. The result of research showed that audit tenure auditor experience and independency have significant positive effect on audit judgement, task complexity has not significant effect.